(untitled) (Chemical Engineering Research Bulletin, 2008)
Fourier transform infrared spectroscopy is widely being used nowadays to characterize both organic and inorganic species of the coal structure. The applications of FT -IR technique for the characterization of coal and minerals have been discussed in this paper. From the FT -IR investigations Bangladeshi coals are revealed as higher rank of bituminous type and minerals are basically silicious nature. Chemical Engineering Research Bulletin 11 (2007) 51-62